Kepuasan Kerja: Faktor-Faktor yang Mempengaruhi Komitmen Kerja Kakitangan FAMA (Federal Agriculture Marketing Authority) di Negeri Selangor - Mohd Ruhaifi, Md Isa @ Mansor (2011)
This study aims to identify the level of job satisfaction and commitment levels of employees in the organization of the Federal Agricultural Marketing Authority, better known as FAMA (Federal Agricultural Marketing Authority) in Selangor. The main objective of this study is to examine the level of job satisfaction and level of commitment in the organization of staff at FAMA and determine whether there is a significant relationship between job satisfacti- on and commitment in the organization. A total of 73 questionnaires to measure the level of job satisfaction developed as a research instrument that contains 77 questions as a factor and is measured using five Likert Scale satisfaction questionnaire based on the Job Description Index (JDI) by (Smith et al.,1969) and commitment based organizations by the Organizational Commitment Questionnaire (OCQ) by (Mowday et al.,1979). All data obtained were collected and analyzed via inferences descriptive and statistical methods. These findings give the impression that there is significant relationship to the dimensions of job satisfaction in the organization's commitment. Analysis carried out to give the impression that the majority of staff either from a professional management team and support groups have a moderate level of satisfaction, but they give a strong commitment to the organization.